2010
DOI: 10.1016/j.jom.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Co‐opetition, distributor's entrepreneurial orientation and manufacturer's knowledge acquisition: Evidence from China

Abstract: a b s t r a c tBy viewing cooperation and different types of conflicts as "co-opetition" factors in a manufacturerdistributor supply chain, this paper provides a conceptual model for examining the effects of cooperation and conflicts on a manufacturer's knowledge acquisition process and for exploring the moderating effects of a distributor's entrepreneurial orientation on the relationships between co-opetition factors and the manufacturer's knowledge acquisition. This conceptual model is tested with 225 dyad s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
168
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(175 citation statements)
references
References 149 publications
(201 reference statements)
1
168
1
3
Order By: Relevance
“…In fact, so important is the role of EO that in contexts where EO is low, competitive advantage is not secured from employing flexibility and cost resources. This may be why there has been increasing interest in research into the intersection between entrepreneurship and OM (Handfield et al, 2009;Hsu et al, 2011;Kickul et al, 2011;Li et al, 2011); researchers have begun to perceive the criticality of EO.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…In fact, so important is the role of EO that in contexts where EO is low, competitive advantage is not secured from employing flexibility and cost resources. This may be why there has been increasing interest in research into the intersection between entrepreneurship and OM (Handfield et al, 2009;Hsu et al, 2011;Kickul et al, 2011;Li et al, 2011); researchers have begun to perceive the criticality of EO.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Li et al (2011). Past studies like Carr and Pearson (1999), also showed that information access is a key aspect for the buyer-supplier relationship.…”
Section: Resultsmentioning
confidence: 97%
“…At the same time, the manufacturer can invest in activities, such as monitoring the distributor's performance or training its team (Y. Li et al, 2011).…”
Section: Performance Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang Wei [6] based on the perspective of competition and cooperation, proposed the existence of cooperation and competition is an important mechanism to solve the problem of border dilemma. Yuan Li [7] obtained the knowledge acquisition and interaction of the competing type to the participant by studying the factors that influence the knowledge acquisition in the competitive environment, thus highlighting the importance of competition and cooperation to the knowledge management. These scholars have put forward their own viewpoints and innovative achievements on knowledge sharing in different environments, but they have not studied the application of BIM technology to the cross-organizational knowledge sharing mechanism in competing environment.…”
Section: Introductionmentioning
confidence: 99%